Hubungan tingkat pengetahuan dengan kejadian anemia pada ibu hamil di wilayah Puskesmas Godean 1 - Addina Muzayana; Sabar Santoso; Dyah Noviawati Setya Arum (Jurnal Kesehatan Ibu dan Anak, 2016)
Anemia in pregnancies known can be risked, for mother or fetus. Knowledge level of pregnant women ofanemia will be concerned to their behavior to prevent anemia, women behavior to how consume ironsupplement, behavior to keep dayli sanitasi hyegin to be free from wormy, because knowledge can influentbehavior to prevent anemia. More higher pregnant women knowledge of anemia, more less opportunitypregnant women careless to take care theirself. Purpose to know corellation of knowledge level with anemia onpregnant women in region of Puskesmas Godean I subdistrict Godean District Sleman 2012. This study isanalitic observational used cross sestional design. Tehnicque sampling in this study is purposive sampling, istook sample froma population and useddossed cuesionersas instrument. Used Chi-squareasdata analysis.Result The majority of pregnant women aged 25-30 years (65-70%), junior secondary education (47.9%) andmultiparous status (68.8%). The results also showed the majority of respondents (46.8%) and had lessknowledge about anemia, and most (58.3%) had anemia. The results of the analysis using Chi Square shows Pvalue of 0.038 ( < dari 0,05). Conclusion there are a correlation of pregnant women knowledge of anemia withanemia incident